A novel fabrication of nitrogen-containing carbon nanospheres with high rate capability as electrode materials for supercapacitors. Issue 16 (22nd January 2015) - Peng, Hui; Ma, Guofu; Sun, Kanjun; Mu, Jingjing; Zhou, Xiaozhong; Lei, Ziqiang
Abstract : Nitrogen-containing polyaniline-based carbon nanospheres (C-PANI) with diameters of about 200 nm are prepared through a direct carbonization method using polyaniline (PANI) nanospheres as carbon precursors at different temperatures. Abstract : Nitrogen-containing polyaniline-based carbon nanospheres (C-PANI) with diameters of about 200 nm are prepared through a direct carbonization method using polyaniline (PANI) nanospheres as carbon precursors at different temperatures. The PANI nanospheres are synthesized via in situ oxidation polymerization of aniline in the presence of sodium carboxymethyl cellulose as a polymerization template. The C-PANI with 6.69% nitrogen content obtained at 800 °C (C-PANI-800) can achieve a high capacitance of 359 F g −1 at the current density of 1 A g −1 in 6 M aqueous KOH electrolyte, meanwhile maintaining excellent rate capability (81% retention at 20 A g −1 ). Furthermore, a symmetric supercapacitor fabricated with C-PANI-800 electrodes exhibits an energy density of 17.5 W h kg −1 at a power density of 227 W kg −1 and superior cycle stability (only 4% loss after 5000 cycles), operating in the voltage range of 0–1.8 V in 0.5 mol L −1 Na2 SO4 aqueous electrolyte.